Stroke in acute type A aortic dissection: the Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD). (20th July 2020) - Chemtob, Raphaelle A; Fuglsang, Simon; Geirsson, Arnar; Ahlsson, Anders; Olsson, Christian; Gunn, Jarmo; Ahmad, Khalil; Hansson, Emma C; Pan, Emily; Arnadottir, Linda O; Mennander, Ari; Nozohoor, Shahab; et al.
Abstract : Acute type A aortic dissection (ATAAD) is a life-threatening condition for which emergent surgical treatment is essential [1]. Abstract: OBJECTIVES: Stroke is a serious complication in patients with acute type A aortic dissection (ATAAD). Previous studies investigating stroke in ATAAD patients have been limited by small cohorts and have shown diverging results. We sought to identify risk factors for stroke and to evaluate the effect of stroke on outcomes in surgical ATAAD patients. METHODS: The Nordic Consortium for Acute Type A Aortic Dissection database included patients operated for ATAAD at 8 Scandinavian Hospitals between 2005 and 2014. RESULTS: Stroke occurred in 177 (15.7%) out of 1128 patients. Patients with stroke presented more frequently with cerebral malperfusion (20.6% vs 6.3%, P  < 0.001), syncope (30.6% vs 17.6%, P  < 0.001), cardiogenic shock (33.1% vs 20.7%, P  < 0.001) and pericardial tamponade (25.9% vs 14.7%, P  < 0.001) and more often underwent total aortic arch replacement (10.7% vs 4.7%, P  = 0.016), compared to patients without stroke. In the 86 patients presenting with cerebral malperfusion, 38.4% developed stroke. Thirty-day and 5-year mortality in patients with and without stroke were 27.1% vs 13.6% and 42.9% vs 25.6%, respectively. Stroke was an independent predictor of early- [odds ratio 2.02, 95% confidence interval (CI) 1.34–3.05; P  < 0.001] and midterm mortality (hazard ratio 1.68, 95% CI 1.27–2.23; P  < 0.001). CONCLUSIONS: Stroke in ATAAD patients is associated with increased early- and midterm mortality. Preoperative cerebral malperfusion and impaired haemodynamics, as well as total aortic arch replacement, were more frequent among patients who developed stroke. Importantly, a large proportion of patients presenting with cerebral malperfusion did not develop a permanent stroke, indicating that signs of cerebral malperfusion should not be considered a contraindication for surgery.